Direct observation of mixed-parity excited states in surface-passivated PbS nanocrystals - Fernee, M; Watt, A; Warner, J; Heckenberg, N; Rubinsztein-Dunlop, H (2004)
Photoluminescent emission is observed from surface-passivated PbS nanocrystals following the two-photon excitation of high-energy excitonic states. The emission appears directly at the excitation energy with no detectable Stokes-shift for a wide range of excitation energies. The observation of direct emission from states excited by two-photon absorption indicates that the parity of the excited states of surface-passivated PbS nanocrystals is partially mixed.